Crossing alone the Mediteranean sea. Some critical issues about unaccompanied minors in Europe - Valtolina, Giovanni Giulio (2018)
Despite the increasing social impact of unaccompanied migrant minors (UAMs) in many European Union (EU) member states, EU regulations on UAMs are still inadequate and the necessary protection measures are thus insufficient. More specifically, the “best interest of the child”, stated in a large number of international documents, may not be properly guaranteed. In addition, there is often a discrepancy between the rights of migrant children, according to the international legislation, and the actual protection they receive. Moreover, despite the declared aim of reaching a common standard of reception and inclusion, policies and practices across Europe are still very different. The paper attempts to highlight and discuss some critical issues regarding UAMs in Europe. Over and beyond the need for the EU to develop a common framework, greater efforts should be made in order to improve inclusion of UAMs, especially to ensure the management of the phenomenon beyond the current...